ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BANK INDONESIA (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bank Indonesia Tahun 2010-2012) - Temmy Muhas Pribadi, 10.05.52.0150; Maskur, Ali (Students Journal of Accounting and Banking, 2014)
This study aims to determine the Comparative Analysis of Financial Performance of Islamic Banking with Conventional Banking Registered in Bank Indonesia. The population in this study is a banking company that is listed in the 2010-2012 Indonesian banks. The samples in this study were taken by purposive sampling method. Data were analyzed using Independent sample t test. The results showed that the CAR, NPL, and LDR significant difference between Islamic banking and conventional banking. only variable ROA and BOPO were no significant differences between Islamic banking and conventional banking. The test as a whole is represented by performance variables showed that there was no significant difference between Islamic banking and conventional banking. However, the overall performance of Islamic banking is better than the conventional banking banking in the study period.Keywords: CAR, ROA, NPL, LDR, BOPO